2015
DOI: 10.1002/chem.201502921
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Phosphorus‐Substituted Rhodamine with Emission Wavelength above 700 nm for Bioimaging

Abstract: Phosphorus has been successfully fused into a classic rhodamine framework, in which it replaces the bridging oxygen atom to give a series of phosphorus-substituted rhodamines (PRs). Because of the electron-accepting properties of the phosphorus moiety, which is due to effective σ*-π* interactions and strengthened by the inductivity of phosphine oxide, PR exhibits extraordinary long-wavelength fluorescence emission, elongating to the region above 700 nm, with bathochromic shifts of 140 and 40 nm relative to rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
112
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 52 publications
2
112
0
2
Order By: Relevance
“…However, only a few polyaromatic materials based on these heterocycles have been reported to date . Examples are the phospha‐rhodamine and the phospha‐fluorescein, which possess a fused π‐extended framework and a λ 5 ‐σ 4 phosphorus center. These molecules illustrate the potential of six‐membered phosphorus rings for materials applications, in particular, as potential pH sensors for biological media and in vivo biomarkers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few polyaromatic materials based on these heterocycles have been reported to date . Examples are the phospha‐rhodamine and the phospha‐fluorescein, which possess a fused π‐extended framework and a λ 5 ‐σ 4 phosphorus center. These molecules illustrate the potential of six‐membered phosphorus rings for materials applications, in particular, as potential pH sensors for biological media and in vivo biomarkers .…”
Section: Introductionmentioning
confidence: 99%
“…Examples are the phospha‐rhodamine and the phospha‐fluorescein, which possess a fused π‐extended framework and a λ 5 ‐σ 4 phosphorus center. These molecules illustrate the potential of six‐membered phosphorus rings for materials applications, in particular, as potential pH sensors for biological media and in vivo biomarkers . Simultaneously, we reported a new synthetic protocol to access novel polyaromatic systems containing a versatile λ 3 ‐σ 3 phosphorus center: the phosphaphenalenes .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al. reported phosphorus‐substituted rhodamines (PRs) as NIR fluorophores, and showed that their LUMO energy levels are lower than those of SiRs . So, we anticipated that the fluorescence emission of PRs might be more easily controlled than that of SiRs, because the fluorophore having the lower LUMO energy level should be a better intramolecular PeT acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…For biological and medicinal applications, fluorescent near-infrared probes are more adequate, due to the reduced interference with the self-fluorescence of the biological material, in addition to less harming effects induced by light at wavelengths longer than 600 nm. [1][2][3][4] Molecules possessing an oxazine ring as a part of a tetracyclic aromatic structure are called benzophenoxazines, and their derivatives having adequate substituents, namely the most well-known, Nile Blue, are associated with an absorbance and a fluorescence emission at longer wavelengths, belonging to the group of near-infrared fluorescence probes. 5 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, several studies with different families of heterocyclic systems have been reported, and all are necessary and extremely important. 4 A localized fluorescence signal was still detected 48 hours after the intramuscular injection in mice of one of these compounds, despite the decay in the fluorescence intensity.…”
mentioning
confidence: 96%